(untitled) (Journal of the College of Basic Education, 2025)
This study aims to uncover the textual function of verbal evidence in the Holy Qur’an through the lens of Qur’anic coherence, which highlights the interconnectedness of verses and surahs. This perspective reveals the Qur’anic text as a linguistic entity with multiple meanings and interwoven connections. The study seeks to delve into the world of the Qur’anic text and its coherence by examining the book nazm Al-Durar fi tanasub Al-ayat Wal-Suwar by Al-Biqam’i . It explores the extent of harmony and consistency achieved by the Qur’anic words and their linguistic meanings through their textual function. This is analyzed using the standards of cohesion and coherence. The study is divided into two sections: The first is theoretical, covering the definitions of key terms such as verbal evidence, text, cohesion, coherence in contemporary linguistic studies, and Qur’anic coherence. The second is applied, focusing on Al-biqa’I’s use of Qur’anic coherence both across multiple verses and within individual surahs